Factors Affecting Patients’ Attitudes and Behavioral Intentions Toward Using Hospital Online Services in Shanghai, China - Li, Jutang (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: The research aimed to examine the factors affecting patients’ attitudes and behavioral intentions toward using hospital online services. The conceptual framework is grounded based on Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) to understand the attitudes and behavioral intention of patients. Research design, data and methodology: The study employed a non-probability sampling procedure to select participants. A questionnaire was developed using a Five-point Likert scale and tested for content validity and reliability through Item-Objective Congruence (IOC) and Cronbach’s Alpha. Confirmatory Factor Analysis (CFA) was conducted to ensure the model’s validity, and Structural Equation Modeling (SEM) was utilized to assess the model fit and test the hypotheses. Results: The analysis confirmed that satisfaction, social influence, promotion conditions have significant direct impact on behavioral intentions, and perceived usefulness and perceived usefulness have significant indirect impact on behavioral intentions through attitude. Conclusions: The research results found that satisfaction, social influence, promotion condition, perceived usefulness, perceived ease of use, and attitude significantly influence the patients’ behavioral intention to use online registration systems, which indicates the significant function of these factors in developing digital health service adoption.